Application of Card Sort Method on Learning History at MA Al-Amin Tabanan Bali - Ismail, Syarof Nursyah; Arifin, Haris Nursyah (Widya Balina, 2024)
This research aims to explore and analyze the implementation of the Card Sort method in history learning at MA Al-Amin Tabanan Bali as an effort to enhance student motivation, interest, activity, and improve student learning outcomes. A descriptive qualitative approach was used to collect data through observation, interviews, and documentation. The results showed that the implementation of the Card Sort method successfully increased student engagement in history learning, accelerated understanding of the material, and created a more interactive and engaging learning atmosphere. Teachers acted as active facilitators who provided direct guidance and feedback to students, as well as facilitated group discussions. Additionally, this method also encouraged collaboration among students and developed their social skills. The findings of this research support the claim that the implementation of the Card Sort method has a significant positive impact on enhancing student learning motivation, learning outcomes, and overall learning quality. The practical implications of this research are that the Card Sort method can be an effective alternative in history learning, especially in the context of MA Al-Amin Tabanan Bali, and contribute to the development of innovative and student-oriented learning strategies. This research also provides a basis for further research in the field of education to better understand and evaluate the effectiveness of different learning methods.